THE EFFECT OF SELF-ASSESMENT ON STUDENTS’ SELF-EFFICACY AND WRITING COMPETENCY - Mona Jiwandani; Lokita Purnamika Utami; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2021)
ABSTRACTIn this Covid 19 pandemic, learning should be done from distance through online learning. This study aims at investigating the effect of self-assessment on students’ self-efficacy and writing competency simultaneously and separately on online learning. To run this research, 52 eleventh grade students of SMAN 1 Sukasada in the academic year 2020/2021 were chosen as the samples. This research applied nonequivalent control group design in which there were two groups compared, namely: self-assessment and conventional assessment. The data of writing competency were collected by using performance test which were then scored by using analytical scoring rubric, meanwhile self-efficacy data were collected by using questionnaire. The collected data were then analyzed by using One Way MANOVA. This research discovered: (1) there is no significant effect of self-assessment on self-efficacy and writing competency simultaneously (p>0.05), (2) there is no significant effect of self-assessment on writing competency separately (p>0.05), and 3) there is no significant effect of self-assessment on self-efficacy separately (p<0.05).